Therapeutic Decision Making in Hepatocellular Carcinoma According to Age and Child–Pugh Class: A Nationwide Cohort Analysis in South Korea - Park, Sunmin; Rim, Chai Hong; Jung, Young Kul; Yoon, Won Sup (Canadian Journal of Gastroenterology and Hepatology, 2021)
Background. We sought to analyze the preferred treatment modality by age and liver function in South Korea. Methods. The Korean Liver Cancer Study Group randomly extracted the data of patients with hepatocellular carcinoma (HCC) enrolled in the Korean Central Cancer Registry from 2008 to 2014 from approximately 50 hospitals nationwide. After excluding distant and lymphatic metastases, the treatment preference for patients with a single lesion (excluding PVT (portal vein thrombosis), hepatic vessels, and bile duct invasion) and with PVT was evaluated in 7559 patients. Patients were grouped by age, and baseline liver function was divided based on the Child–Pugh class (CPC) A, B, and C. Results. For a single HCC, the majority of patients selected transarterial therapy as the initial treatment, followed by surgical resection and local ablative therapy. The surgical resection rate decreased significantly with age (p<0.001), and the transarterial therapy rate significantly increased (p<0.001). For CPC C, liver transplantation was significantly increased to 11.5%, and 36.3% of patients received no treatment. In HCC with PVT, the transarterial therapy rate was the highest, followed by the rate of abandonment of treatment. The proportion of no treatment significantly increased with age (p<0.001). In CPC C, transarterial therapy and systemic therapy were attempted in 15.4% and 5.8% of patients, respectively. Conclusions. Age and liver function have a significant impact on the therapeutic decision-making of HCC patients in Korea. In unfavorable conditions, surgical resection was less favored in patients with single tumors, and no treatment was preferred in patients with PVT.